Novel polyacrylate-based cationic nanoparticles for survivin siRNA delivery combined with mitoxantrone for treatment of breast cancer. Issue 6 (November 2016) - Arami, Sanam; Mahdavi, Majid; Rashidi, Mohammad Reza; Fathi, Marziyeh; Hejazi, Mohammad-saeid; Samadi, Nasser
Abstract: As a gene delivery method in breast cancer therapy, knocking down the undesired genes in the cancerous cells would be promising. Inhibitors of Apoptosis Protein (IAP) family genes are some of the genes whose responsibility is inhibition of apoptosis in cells. Silencing these genes seems to be helpful directing the tumor cells to death. siRNA sequence designed against survivin anti-apoptotic gene can play this role if carried to the cytoplasm. Here we prepared a positive charged biocompatible nano-sized particle made up of a Fe3 O4 core covered respectively by polyacrylate (PA) and polyethyleneimine (PEI) layer, which could successfully deliver the siRNA into the MCF-7 cells. The particle structure was checked and having less than 50 nm diameter in size, positive charge and, safety towards MCF-7 cells besides being able to form nanoplexes with the siRNA strand helps it entering into the biologic assays part. The siRNA delivery evaluated via flowcytometry. Apoptosis induction was determined by DAPI staining. The efficiency of survivin gene knockdown was evaluated in mRNA and protein levels using Real time PCR and western blotting methods. Overall, the Fe3 O4 -PA-PEI nanoparticles can deliver siRNA effectively into the cytoplasm of the MCF-7 breast cancer cells and induce apoptosis.